The Function of Bevelled-Rim Bowls. A Case Study at the TUV Mound, Tal-e Malyan, Iran - Nicholas, Ilene Mildred
ersch. 1988; résumé français; bowls were not ration bowls, but rather bowls used in the paying of taxes.